Effect of mineral water from Trenčianske Teplice (drinkable source, Drill SB-3) on lipid peroxidation in vitro - Ďurfinová, Monika; Brechtlová, Marta; Kuračka, Ľubomír; Zálešáková, Janka; Čelko, Juraj; Líška, Branislav (Prague Medical Report, 2010)
Influence of mineral water from Trenčianske Teplice (drinkable source) on lipid peroxidation processes was determined in model situations under in vitro conditions using the brain tissue. The central nervous system was selected because it is especially sensitive to the radical-induced damage. In addition, there is a high content of polyunsaturated fatty acids in the brain which has a low antioxidant capacity and is relatively rich in iron ions – enhancers of lipid peroxidation processes. We present the inhibitory effect of the mineral water on the intensity of lipid peroxidation in the presence of iron ions. We assume that some component or combination of more components of the mineral water may act as chelators of iron ions.
Keywords: Iron; mozek; Brain; zvířata; Rats; látky reagující s kyselinou thiobarbiturovou; Financing, Organized; financování organizované; Lipid Peroxidation; mužské pohlaví; železo; Rats, Wistar; minerální vody; krysa rodu Rattus; peroxidace lipidů; potkani Wistar; Animals; Thiobarbituric Acid Reactive Substances; Mineral Waters; Male